Designing a trust evaluation model for open‐knowledge communities. (4th July 2013) - Yang, Xianmin; Qiu, Qin; Yu, Shengquan; Tahir, Hasan
Abstract The openness of open‐knowledge communities (OKCs) leads to concerns about the knowledge quality and reliability of such communities. This confidence crisis has become a major factor limiting the healthy development of OKCs. Earlier studies on trust evaluation for Wikipedia considered disadvantages such as inadequate influencing factors and separated the treatment of trustworthiness for users and resources. A new trust evaluation model for OKCs—the two‐way interactive feedback model—is developed in this study. The model has two core components: resource trustworthiness (RT) and user trustworthiness (UT). The model is based on more interaction data, considers the interrelation between RT and UT, and better represents the features of interpersonal trust in reality. Experimental simulation and trial operation for the Learning Cell System, a novel open‐knowledge community developed for ubiquitous learning, show that the model accurately evaluates RT and UT in this example OKC environment.